2018
DOI: 10.1051/e3sconf/20184400093
|View full text |Cite
|
Sign up to set email alerts
|

Freely available daily hydrometeorological data from Czechia: further insights

Abstract: Abstract. Quite recently, freely available mean daily discharge series representing the territory of Czechia were complemented by ten daily series of nine climate variables, spanning usually from 1961 to the present. Their length thus allows the analyses similar to those conducted approximately a year ago in relation to the long series of discharge. Besides this possibility, the current paper goes further and shows how these long series (including discharge) can be used in order to assess the presence of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Furthermore, it was found that many series involving indices related to hydrological drought in Czechia reveal high values of H as well, which was confirmed by unit root tests. On the other hand, precipitation series in Czechia for the period 1961-2012 showed no LTP (Ledvinka, 2015c). The differences between discharge and climate variables from this point of view, using selected stations within the Czech part of the Elbe basin, were highlighted also in Ledvinka and Jedlicka (2018).…”
Section: Overview Of Studies Performed In the Elbe Basinmentioning
confidence: 94%
“…Furthermore, it was found that many series involving indices related to hydrological drought in Czechia reveal high values of H as well, which was confirmed by unit root tests. On the other hand, precipitation series in Czechia for the period 1961-2012 showed no LTP (Ledvinka, 2015c). The differences between discharge and climate variables from this point of view, using selected stations within the Czech part of the Elbe basin, were highlighted also in Ledvinka and Jedlicka (2018).…”
Section: Overview Of Studies Performed In the Elbe Basinmentioning
confidence: 94%